Characterization of gas-liquid flows in stirred vessels using pressure and torque fluctuations - Khopkar, A. R.; Panaskar, S. S.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2005)
Gas-liquid flows in a stirred vessel exhibit different flow regimes and demonstrate complex interaction of transport processes with varying spatio-temporal scales. The knowledge of key space and time scales of fluid dynamics is important for designing and enhancing the performance of gas-liquid stirred reactor. The present study uses simple, robust, and nonintrusive experimental techniques (torque and pressure sensors) to characterize the fluid dynamics in a gas-liquid stirred vessel. Time series obtained from the pressure and torque sensors were analyzed to develop criteria for flow regime identification. Further analyses of torque and pressure time series were done to extract valuable information of different time scales of fluid dynamics. The detailed analysis of torque and wall pressure fluctuations provided not only an insight into the fluid dynamics but also a possible opportunity to on-line monitoring of gas-liquid flows in stirred vessel.

Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF

Gas-liquid flow generated by a Rushton turbine in stirred vessel: CARPT/CT measurements and CFD simulations - Khopkar, A. R.; Rammohan, A. R.; Ranade, V. V.; Dudukovic, M. P. (Chemical Engineering Science, 2005)
In this work, computer-automated radioactive particle tracking (CARPT), computed tomography (CT) and computational fluid dynamic (CFD) based models were used to investigate gas-liquid flow generated by a Rushton turbine. CARPT and CT measurements were carried out in a gas-liquid stirred vessel operating in two different flow regimes and captured the quantitative Eulerian information of gas-liquid flow. The CARPT data was then used to extract the circulation tune distribution in a vessel. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence (along the lines proposed by Brucato et al. (Chem. Eng. Sci. 45(1998) 3295)) were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). Most model predictions compared favourably with CARPT and CT measurements. Validated CFD models as attempted in this paper are promising to simulation of industrial stirred vessels. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CARPT; CFD; CT; gas-liquid flow; stirred vessel

Hydrodynamics of trickle-bed reactors: experiments and CFD modeling - Gunjal, P. R.; Kashid, M. N.; Ranade, V. V.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
{Hydrodynamics of trickle-bed reactors involve complex interactions of gas and liquid phases with packed solids. Such complex interactions manifest in different flow regimes occurring in trickle-bed reactors. Knowledge of prevailing flow regime, pressure drop, and liquid holdup is essential for design and performance evaluation of the reactor. Detailed knowledge of fluid dynamics is essential for ``a priory'' predictions as well as for interpretation of available data. In this study, we have used wall pressure fluctuation measurements to identify prevailing flow regime in trickle beds. Experiments were carried out on two scales of columns (of diameter 10 cm and 20 cm) with two sets of particles (3 min and 6 mm diameter spherical particles). Effects of prewetted and unwetted bed conditions on pressure drop and liquid holdup were reported for a range of operating conditions (V-G = 0.22-0.44 kg/m(2)s

Modeling of rotary desiccant wheels - Harshe, Yogesh M.; Utikar, R. P.; Ranade, V. V.; Pahwa, D. (Chemical Engineering & Technology, 2005)
Rotary desiccant wheels are widely used in dehumidification and energy recovery applications. In this work, we have developed a 2D, steady state model of a rotary desiccant wheel. Mass and energy balance equations for the air streams and the desiccant wheels were developed. The hydraulic diameter and surface area for heat and mass transfer were calculated based on knowledge of the flute geometry. Appropriate correlations for the Sherwood number and Nusselt number were used to estimate heat and mass transfer coefficients. The model is capable of predicting steady state behavior of desiccant wheels having at the most three sections (process, purge, and regeneration). The mathematical model was validated using a real desiccant wheel, and the calculation results are in reasonable agreement with the experimental data. Based on this model, the temperature and humidity profiles in the wheel during both the dehumidification and the regeneration processes are analyzed. The simulated results were used to gain an insight into the operation of desiccant wheels. The model and the presented results will be useful for optimizing dehumidification and energy recovery applications.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Modeling of vaporization and cracking of liquid oil injected in a gas-solid riser - Nayak, S. V.; Joshi, S. L.; Ranade, V. V. (Chemical Engineering Science, 2005)
Vaporization and cracking of liquid oil injected in a gas-solid riser (fluid catalytic cracking riser reactor) was computationally studied in this work. Evaporation of a single drop injected in a stream of gas-solid mixture was analyzed first. A model for simulating evaporation of a drop considering heat transfer from the gas phase as well as from the solid particles was developed. The model relates the evaporation rate of droplet with rate of collisions of solid particles, specific heat capacities of solid and liquid, latent heat of vaporization, relative velocity of gas and liquid and temperatures of three phases. The understanding gained from such a model was then extended to simulate evaporation of liquid drops injected in FCC risers. The Eulerian-Lagrangian approach was used to simulate simultaneous evaporation and cracking reactions occurring in FCC riser reactors. A commercial CFD code, FLUENT (of Fluent Inc., USA) was used. Four and ten lump models were used for simulating cracking reactions. Appropriate user defined functions were developed to implement heterogeneous kinetics and heat transfer models in FLUENT. A special algorithm was developed to calculate accumulated coke on catalyst particles. A boiling point range was considered for simulating realistic oil feedstock. The model was first evaluated by comparing predicted results with published industrial data. The simulations were then carried out to understand influence of key design and operating parameters on performance of FCC riser reactors. The parameters studied included; initial oil droplet distribution, catalyst inlet temperature, catalyst to oil ratio and thermal cracking. The approach, model and results presented here would be useful for optimization of FCC operation, cost to benefit analysis of new FCC nozzles and related decision-making. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cracking reactions; Evaporation; FCC; heat transfer; riser

CFD simulation of gas-liquid stirred vessel: VC, S33, and L33 flow regimes - Khopkar, A. R.; Ranade, V. V. (AICHE Journal, 2006)
A comprehensive computational model based on the Eulerian-Eulerian approach was developed to simulate gas-liquid flows in a stirred vessel. A separate submodel was developed to quantitatively understand the influence of turbulence and presence of neighboring bubbles on drag acting on bubbles. This submodel was used to identify an appropriate correlation for estimating the interphase drag force. The standard k-epsilon turbulence model was used to simulate turbulent gas-liquid flows in a stirred vessel. A computational snapshot approach was used to simulate motion of the standard Rushton turbine in a fully baffled vessel. The computational model was mapped onto FLUENT4.5, a commercial CFD solver. The model predictions were compared with the previously published experimental data of Bombac and co-workers. The model was used to simulate three distinct flow regimes in gas-liquid stirred vessels: vortex clinging (VC), alternating small cavities (S33), and alternating large cavities (L33). The predicted results show reasonably good agreement with the experimental data for all three regimes. The computational model and results discussed in this work would be useful for understanding and simulating gas holdup distribution and flow regimes in stirred vessels. (c) 2006 American Institute of Chemical Engineers.
Keywords: computational fluid dynamics (CFD); Flow regimes; gas holdup distribution; Rushton turbine; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

Computational fluid dynamics simulation of the solid suspension in a stirred slurry reactor - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the standard k-epsilon turbulence model with mixture properties to simulate the turbulent solid-liquid flow in a stirred reactor. A multiple reference frame approach was used to simulate the impeller rotation in a fully baffled reactor. A computational model was mapped on to a commercial CFD solver FLUENT6.2 (of Fluent Inc., USA). The model predictions were compared with the published experimental data of Yamazaki et al. [Powder Technol. 1986, 48, 205] and Godfrey and Zhu [AIChE Symp. Ser. 1994, 299, 181]. The predicted results show reasonably good agreement with the experimental data. The computational model and results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.

Modeling of rotary cement kilns: applications to reduction in energy consumption - Mujumdar, Kaustubh S.; Arora, Amit; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
Rotary cement kilns are used for converting calcineous raw meal into cement clinkers. In this paper, we discuss and evaluate possible ways of reducing energy consumption in rotary cement kilns. A comprehensive one-dimensional model was developed to simulate complex processes occurring in rotary cement Kilns. A modeling strategy comprising three submodels. viz. a model for simulating the variation of bed height in the kiln, a model for simulating reactions and heat transfer in the bed region, and a model for simulating coal combustion and heat transfer in the freeboard region, was developed. Melting and formation of coating within the kiln were accounted for. Combustion of coal in the freeboard region was modeled by accounting for devolatilization, finite-rate gas-phase combustion, and char reaction. The simulated results were validated with the available data from three industrial kilns. The model was then used to understand the influence of various design and operating parameters on kiln performance. Several ways of reducing energy consumption in kilns were then computationally investigated. The model was also used to propose and to evaluate a practical solution of using a secondary shell to reduce energy consumption in rotary cement kilns. Simulation results indicate that varying kiln operating variables, viz. solid flow rate or RPM, can result only in small changes in kiln energetics. Use of a secondary shell over the kiln and energy recovery by passing air through the annular gap between the two appears to be a promising way to achieve significant energy savings. The developed model and the presented results will be useful for enhancing the performance of rotary cement kilns.

Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

CFD simulation of gas-liquid flows in a reactor stirred by dual rushton turbines - Kasat, Gopal R.; Pandit, Aniruddha B.; Ranade, V. V. (International Journal of Chemical Reactor Engineering, 2008)
In the present work, we have simulated gas-liquid flows in a tall stirred reactor equipped with dual Rushton turbines. A two fluid model along with the standard k-epsilon turbulence model and modified drag coefficient, (proposed by Khopkar & Ranade, 2006) accounting for the effect of bulk turbulence, was used to simulate the dispersed gas-liquid flow in a stirred reactor. The multiple reference frames (MRF) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc. USA). The model was used to simulate three distinct flow regimes in a gas-liquid stirred reactor: L33-VC (lower impeller-upper impeller), S33-VC and VC-VC. The model predictions were compared with the published experimental data of Bombac & Zun (2000). The predicted results show good agreement with the experimental data for all the three flow regimes. The computational model presented in this work would be useful for simulating different flow regimes in a gas-liquid stirred vessel.
Keywords: computational fluid dynamics; dual Rushton turbine; Flow regimes; gas hold-up distribution; stirred reactor

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor

Flow pattern in vortex diode: experiments and CFD simulations - Kulkarni, Amol A.; Ranade, V. V.; Rajeev, R.; Koganti, S. B. (AICHE Journal, 2008)
Vortex diodes are used as leaky nonreturn valves in applications, where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no detailed analysis of the flow inside the vortex diodes is available. A strategy was derived for the CFD simulations of the vortical flow in diodes. A good agreement was seen between pressure drop (Delta P) across the inlet-outlet ports from CFD simulations, and the experimental data for five diode sizes. The simulations showed that in the reverse flow situation tangential velocity was dominant and resulted in conservation of angular momentum in the chamber until it reaches the axial exit port. This vortical motion induced a significant pressure drop (Delta P-r). The axial velocity gradient over the chamber cross-section helps in inducing relaminarization of the flow. In the forward flow mode, the fluid gets distributed radially over the chamber and exits through the tangential port, yielding low Delta P-f. The analysis showed that the performance of a diode is strongly affected by diode geometry, size, aspect ratio, nozzle configuration and Reynolds number. Among different configurations, the nozzles with entry port size equal to diode yielded higher diodicity. Simulations showed that using angle of divergence for diffuser sections of nozzles of the order of 7 degrees exhibited higher diodicity than smaller angles. It was also observed that at higher flow rates significantly higher diodicity was obtained using axial nozzles with larger radius of curvature for expander section. The modeling methodology and results presented will be useful for evolving better designs of vortex diodes.
Keywords: CFD; Diodicity; pressure drop; relaminarization; Vortex diode

CFD Simulation of bubble columns: modeling of nonuniform gas distribution at sparger - Rampure, M. R.; Mahajani, S. M.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2009)
Most laboratory bubble columns are equipped with sieve plate spargers. The sieve plate spargers are known to lead to nonuniform gas distribution. It is important to account for such nonuniform gas distribution at the sparger in the computational model before experimental data collected from such columns are used to fit the model parameters. In this article, such an attempt is made. A detailed, 3D CFD model was developed to simulate unsteady gas-liquid flows in bubble Columns with sieve plate spargers. The sensitivity of the nonuniformity of gas distribution at the sparger with sparger resistance was examined. The model predictions were compared with the experimental data. The developed model and presented results will be useful for Simulating industrial bubble columns.

Reply to the ``comments to CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers and part II: axial flow impellers, multiple impellers and multiphase dispersions'' - Joshi, J. B.; Nere, N. K.; Rane, C. V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, A. W.; Ranade, V. V. (Canadian Journal of Chemical Engineering, 2012)

Catalysis and catalytic processes - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst that provides an alternative route of reaction with lower activation energy and better control of selectivity can make a substantial impact on process viability and economics. In this chapter, the basics of catalysis and catalytic processes are introduced. Some aspects of reaction and reactor engineering required to realize catalytic processes in practice are also discussed. In addition, the organization of the book is outlined.

Catalysis for fine and specialty chemicals - Joshi, S. S.; Bhatnagar, A.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
The fine and specialty chemical industry is extremely diverse, encompassing pharmaceuticals, dyestuffs, food additives, agrochemicals, polymer additives, flavors and fragrances, various chemical intermediates, etc. Fine and specialty chemicals have been around for more than 100 years and they are produced with the aim of either being used as is or in the form of additives/formulations. These organic chemicals are generally manufactured in batch or semibatch processes. Most of these generally involve multistep processes and often generate significant by-products/effluents per kg of useful products. Catalysis can be effectively used to reduce such waste generation and to minimize consumption of raw materials. In this chapter, we present various applications of homogeneous, as well as heterogeneous catalysis and catalytic processes, which are particularly relevant to fine and specialty chemicals

Catalytic reaction engineering - Gunjal, P. R.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
hemical reaction engineering has contributed remarkably in bringing laboratory-developed chemistry into commercial practice. Reaction engineering is useful for analysis of reactions, identifying rate-limiting steps, determining overall rates, selection of reactor configuration and design and scale-up of reactors. Reaction engineering also provides useful insights into catalytic cycles and provides clues for improving catalyst systems. It essentially includes all the activities necessary to evolve best possible hardware and operating protocol for the reactor to carry out the desired transformation of raw materials (or reactants) into value-added products. This chapter provides an overview of reaction engineering aspects of catalytic processes.

Characterizing flow and solid suspension in optimax crystallization workstation - Sardeshpande, M.; Pandit, A.; Vedantam, S.; Ranade, V. V. (North American Mixing Forum 2016 - Core Programming Area at the 2016 AIChE Annual Meeting, 2016)

Epilogue - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
This chapter recaptures the key points and the lessons learned from our experience in applying the material discussed in this book to addressing industrially relevant issues. Some comments on future trends in catalysis and catalytic processes are included. We hope that this book will stimulate further work on this very important area from an industrial as well as a scientific point of view.

Industrial catalytic processes for fine and specialty chemicals - Joshi, S. S.; Ranade, V. V. (Elsevier Inc., 2016)
Industrial Catalytic Processes for Fine and Specialty Chemicals provides a comprehensive methodology and state-of-the art toolbox for industrial catalysis. The book begins by introducing the reader to the interesting, challenging, and important field of catalysis and catalytic processes. The fundamentals of catalysis and catalytic processes are fully covered before delving into the important industrial applications of catalysis and catalytic processes, with an emphasis on green and sustainable technologies. Several case studies illustrate new and sustainable ways of designing catalysts and catalytic processes. The intended audience of the book includes researchers in academia and industry, as well as chemical engineers, process development chemists, and technologists working in chemical industries and industrial research laboratories. Discusses the fundamentals of catalytic processes, catalyst preparation and characterization, and reaction engineering Outlines the homogeneous catalytic processes as they apply to specialty chemicals Introduces industrial catalysis and catalytic processes for fine chemicals Includes a number of case studies to demonstrate the various processes and methods for designing green catalysts.

Ion exchange resin catalyzed reactions-An overview - Bhandari, V. M.; Sorokhaibam, L. G.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
This chapter gives an overview of ion exchange resins as catalyst for a variety of reactions. Emphasis is placed on the use of resin as a catalyst rather than on reactions. Various aspects of resin catalysis, such as types of reactions where resin can be used, the physical form of resin and activity, and issues pertaining to its application as a catalyst are discussed. Advantages and disadvantages of resins as catalyst for different types of reactions are highlighted. Aspects like reactor configurations, selection of resin, process integration, process separations and the environmental impact of using resins as catalysts are also included. Possible future developments in the ion exchange catalysis area are also highlighted.

Three-phase slurry reactors - Buwa, V. V.; Roy, S.; Ranade, V. V. (Multiphase catalytic reactors: theory, design, manufacturing, and applications, 2016)
Many of the chemical reactors employed in various sectors of the process andchemical industries, suchas petroleumrefining,downstream processing and petrochemicals, bulk and specialty chemicals, and pharmaceuticals, involve reactants and products in three phases. The ubiquitous presence of three-phase reactors comes from the fact that many of the reactants are liquids under reaction conditions, to be treated with a gas like hydrogen, and in the presence of a heterogeneous catalyst that is usually a solid. This requirement leads to two broad modes of contacting one in which the catalyst is held stationary in a "fixed" or a "packed bed" and one in which the catalyst is set free to move, along with the flowing fluid phases, during their sojourn through the reactor vessel.The choice ofwhether the catalyst should be fixed ormoving is usually dictated by the relative dominance of transport rates and intrinsic kinetics. If the reaction chemistry is intrinsically slow (when external and internalmass transfer of chemical species from the fluid phases to the porous catalyst is not rate limiting), packed bed reactor that allows very high catalyst loading is usually preferred. Packed beds, however, do not constitute the main topic of discussion in this monograph. Still, three-phase packed beds and slurry reactors are really parts of the same continuum of three-phase catalytic reactors andhave beendiscussedcomprehensively about three decades back in the classic book by P.A. Ramachandran and R.V. Chaudhari (Three Phase Catalytic Reactors. NewYork:Gordon and Breach Science Publishers; 1983). The same authors published earlier a review of three-phase slurry reactors (Chaudhari RV, Ramachandran PA. Three phase slurry reactors. AIChE J. 1980;26(2):177-199). This chapter builds on these authors' works and attempts to update the reader on developments in the field over the past few decades while retaining the essential reactionandreactorengineering aspects.The focus isonthe design, scale-up, and operation of three-phase slurry reactor systems

Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation - Suryawanshi, N.B. (Fuel, 2017)
The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves pre-programmed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl radicals for oxidative removal of sulfur. The efficiency of the process is strongly dependent on the nature of device apart from the nature of the organic phase. The effects of process parameters and engineering designs were established for three organic solvents (n-octane, toluene, n-octanol) for model sulfur compound-Thiophene. A very high removal to the extent of 95% was demonstrated. The results were also verified using commercial diesel. The cavitation yield is significantly higher for vortex diode compared to the orifice. The process has potential to provide a green approach for desulfurization of fuels or organics without the use of catalyst or external chemicals/reagents apart from newer engineering configurations for effective implementation of hydrodynamic cavitation in industrial practice and also appears to be economically sustainable.
Keywords: Fuel; Oxidation; Petroleum; Pollution Control; Sulphur Removal

Drying of almonds I: single particle - Chilka, A. G.; Ranade, V. V. (Indian Chemical Engineer, 2017)
Drying is an essential unit operation required in food processing industries, particularly in the dry fruits industry. Drying of almonds exhibit many characteristic features such as non-spherical shape, swelling/ shrinkage as a function of moisture content, uneven drying because of their peculiar shape and proximity to other almond kernels and so on. In this study, we have investigated the drying of almonds through experiments and computational modelling. In this regard, Mettler Toledo Halogen moisture analyzer unit was used to conduct experiments for a single almond kernel. In this widely used equipment, internal air flow patterns and therefore heat and mass transfer depend on natural circulation of air. A detailed three-dimensional computational fluid dynamics (CFD) model was used to simulate the air flow pattern, heat and mass transfer in the drying unit. Carefully designed experiments with a single almond kernel were carried out at different temperatures to estimate key parameters of interest (drying kinetics and effective diffusivity). The CFD model was also used to quantify non-uniform heat and mass transfer and therefore non-uniform drying of a single almond kernel. The presented approach, models and results might be useful to improve the performance of drying units in industrial systems. The results and models presented here will also provide a basis for further work on multiple almond kernels and on tray dryer unit. © 2017 Indian Institute of Chemical Engineers

Drying of almonds II: multiple particles - Chilka, A. G. (Indian Chemical Engineer, 2017)
Computational modelling is an efficient and effective tool for modelling the drying process for food products. Developing validated computational models for drying processes is essential to build energy-efficient drying units, producing uniform quality of dried products. This work presents drying behaviour of almonds with a specific focus on understanding interaction among multiple almonds. Eight (2 × 2 × 2) particles and twenty seven (3 × 3 × 3) particles arranged in the shape of a cuboid were used to conduct drying experiments in a Mettler Toledo Moisture Analyzer unit. Experiments were conducted to measure the moisture loss data with respect to drying time using almond kernels. Experimental data were used to understand drying kinetics as well as variation in moisture content with respect to their positions in a cuboid. Computational fluid dynamics based simulations were carried out for the flow, heat transfer and drying of particles in the unit. Actual geometry of individual particles was considered in simulations to predict the variation in velocity, heat and mass transfer coefficients for all the particles. Simulations predicted moisture loss data that matches well with the experimentally measured values. Average moisture for each layer was also compared for various intermediate drying times. Simulation results captured the overall drying process for multiple particles system adequately. The results are compared with the results obtained with drying of a single almond. The approach, models and presented results will be useful for designing large-scale drying units for almonds. © 2017 Indian Institute of Chemical Engineers
Keywords: Almonds; CFD; Drying

Estimation of gas induction in jet loop reactors: influence of nozzle designs - Sharma, D.V. (Chemical Engineering Research and Design, 2017)
Jet loop reactors are used widely for conducting gas liquid reactions because of the high mass transfer achieved in the gas–liquid ejector. Studies have shown that the mass transfer has a very strong correlation to the amount of gas induced in the ejector, and hence it is important to understand gas induction to enhance the performance of any gas–liquid nozzle. In this work, we used a single phase CFD model of the ejector with one adjustable parameter for estimating gas induction rates. After establishing that the model adequately describes the experimental data, the model was used for a quick evaluation of ejector geometries. Influence of key geometric parameters of gas–liquid ejectors like nozzle diameter, mixing tube length, distance between the nozzle outlet and mixing tube, suction chamber geometry and diffuser angle was investigated. It was found that dependence of gas induction on geometric parameters like distance between nozzle—mixing tube, suction chamber geometry, diffuser angle was either weak or had a clear maxima at or beyond a certain value of the geometric parameter. Other parameters like mixing tube length and nozzle diameter have a more complex impact on gas induction. The presented approach and results will be useful for quantifying influence of nozzle designs on gas induction rate in jet loop reactors.
Keywords: CFD; Gas Induction; Jet Loop Reactors; Nozzle Geometry

MgFeCe ternary layered double hydroxide as highly efficient and recyclable heterogeneous base catalyst for synthesis of dimethyl carbonate by transesterification - Nivangune, N. T. (Catalysis Letters, 2017)
A series of Mg3:Fex + Ce1−x LDHs (3:1) were synthesized by co-precipitation method by varying molar ratio of Fe:Ce between 1:0 to 0:1 (LDH-1 to LDH-6). All synthesized LDHs were characterized by XRD, FT-IR, TEM, N2 sorption, benzoic acid titration and XPS in detail and evaluated for selective synthesis of dimethyl carbonate by transesterification of ethylene carbonate with methanol. It was demonstrated that the structural and basic properties of synthesized LDHs were strongly dependent on the Fe:Ce molar ratio (Ce concentration). The correlation between their physicochemical properties and catalytic performance was studied in detail. Among all synthesized LDHs the best result was obtained with LDH-3 (Fe:Ce = 0.85:0.15) where LDH structure remained intact, and showed high number of strong basic sites on LDH surface. LDH-3 was recycled 7 times while maintaining high catalyst activity and selectivity towards DMC. The obtained results elucidate the important role of Ce in modifying the basic properties of LDH in enhancing the catalytic activity for DMC synthesis. Graphical Abstract: [Figure not available: see fulltext.]. © 2017, Springer Science+Business Media, LLC.
Keywords: Dimethyl carbonate; ethylene carbonate; Mg–Fe–Ce Ternary Hydrotalcite; transesterification

Modeling and simulation of a fluidized bed gasifier - Jain, A. A.; Mehra, A.; Ranade, V. V. (ASIA-Pacific Journal of Chemical Engineering, 2018)
A mathematical model to simulate continuous gasification of coal particles in a bubbling fluidized bed reactor is presented. Material and energy balance equations have been formulated based on the 2-phase theory. Well-known correlations have been used to estimate the hydrodynamics. Devolatilization, heterogeneous reactions, and homogenous reactions have been included in the model. The model is used to simulate 29 experimental data sets from the published literature. The model predictions agree very well with the experimental data by adjusting the particle size. After establishing agreement with the data, the model was used to investigate influence of various operating parameters on overall performance (carbon conversion and the gross calorific value of generated gas). Thermodynamic analysis (using the minimization of the Gibbs free energy approach) has also been discussed. The presented model and results provide useful tool and insight on design and operation of fluidized bed gasifier.